A competing infection model for the spread of different viewpoints of a divisive idea. Issue 3 (3rd July 2019) - Chisholm, Benjamin R.; Muller, Peter A.; Horn, Amanda J.; Ellis, Zachary S.
ABSTRACT: We develop a non-network, deterministic, competing infections model for the spread of two competing viewpoints of a divisive idea that incorporates external factors in addition to interpersonal interactions. We consider divisive ideas to have polarizing support, i.e. there are no "shades of grey." The proposed model for the spread of the competing support and skepticism of such an idea within a population is based on both epidemiological and competing species models. The model is then analyzed qualitatively and quantitatively in a case study of the 2016 Republican primary polls. Parameter fitting to this data shows the proposed model is plausible for the spread of viewpoints of a divisive idea.